Narrative medicine. The patient as “text”, object and subject of compassion - Rosas Jiménez, Carlos Alberto (Acta Bioethica, 2017)
Narrations have been able to influence medicine, giving rise to a new approach call “narrative medicine”. In this paper we consider the patient as a text, such is, an open book that the physician intervenes, but also from which the physician may and need to learn a lot. To deepen a little in the narrative perspective of patient understanding and his/her situation helps us to discover how the patient is object of compassion by physicians, but also how he/she turns into subject of compassion. We conclude that it is important for physicians to dedicate time in their initial medical training, as well as in their permanent training, to explore and exploit the value of narrations, that help them to categorize their living experiences and that of the patients.